2012
DOI: 10.1128/jb.00563-12
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of the Nitrogen-Fixing Symbiotic Bacterium Bradyrhizobium elkanii 587

Abstract: The draft sequence of the genome of Bradyrhizobium elkanii 587 is presented. This was obtained using Illumina Next-Gen DNA sequencing combined with Sanger sequencing. Genes for the pathways involved in biological nitrogen fixation (the nif gene cluster), nod genes including nodABC, and genes for the type III protein secretion system (T3SS) are present. Bradyrhizobium elkanii 587 is a nitrogen-fixing bacterium that nodulates soybean and is used in commercial inoculants in Brazil (7).The draft genome sequence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 11 publications
(8 reference statements)
2
11
0
Order By: Relevance
“…Similarly, the draft sequence of the genome of B. elkanii 587 revealed the presence of a tts gene cluster similar to that found in B. elkanii USDA 61 (de Souza et al, 2012). Both B. elkanii T3SSs possess nopX , which is absent in the close relative B. japonicum , but it is present in S. fredii strains (Figure 3).…”
Section: Rhizobiasupporting
confidence: 63%
“…Similarly, the draft sequence of the genome of B. elkanii 587 revealed the presence of a tts gene cluster similar to that found in B. elkanii USDA 61 (de Souza et al, 2012). Both B. elkanii T3SSs possess nopX , which is absent in the close relative B. japonicum , but it is present in S. fredii strains (Figure 3).…”
Section: Rhizobiasupporting
confidence: 63%
“…Interestingly, the sequence comparison revealed that none of the nif and nod genes or Symbiosis Islands found in genomes of B. elkanii, B. japonicum and other nitrogen-fixation Bradyrhizobium sp. isolated from soil or plants [18], [28] are present in the genome of OHSU_III. We plan to continue the cultures of the microbes that are alive but in a less-active state in OHSU_III culture.…”
Section: Discussionmentioning
confidence: 99%
“…Genes associated with the symbiotic lifestyle in most of the Bradyrhizobium species are located in their chromosome, with the exception of Bradyrhizobium sp. DOA9 strain, which harbours a 0Á74 Mb symbiotic plasmid containing genes involved in nodulation, nitrogen fixation and type III/IV protein secretion systems (Kaneko et al 2002;de Souza et al 2012;Okazaki et al 2015). Even in the Mesorhizobium species, symbiotic plasmids only could be found in Mesorhizobium huakuii and Mesorhizobium amorphae strains (Kaneko et al 2000;Reeve et al 2013;Wang et al 2014;Haskett et al 2016).…”
Section: Introductionmentioning
confidence: 99%